1982
DOI: 10.1111/j.1570-7458.1982.tb03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Hits and Misses. The Ecological Approach to Pest Control in Orchards

Abstract: Experiments in the Netherlands have shown that over half of the 24 species of arthropod noxious to apple orchards can be controlled fully or substantially by biological or cultural methods. Typhlodromus pyri proved the agent responsible for biological spider mite control. Contrary to the results of earlier experiments in the Netherlands, biological control of spider mites was successful in intensively managed orchards. Modern management of orchards suppresses several other insect pests. An undergrowth of wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 21 publications
2
69
0
3
Order By: Relevance
“…), orchards several researchers have demonstrated the potential for companion plants to increase biological control (Bugg & Waddington, 1994;Jenser et al, 1997;Stephens et al, 1998;Brown & Glenn 1999;Bostanian et al, 2004). Enhancement of aphid biological control on apple has been accomplished with companion plants (Wyss, 1995;Brown et al, 1997) but other research has found no effect of companion plants on aphid populations (Gruys, 1982;Haley & Hogue, 1990;Brown & Glenn, 1999). Interplanting species of fruit trees bearing extrafloral nectaries into apple orchards has also been suggested (Brown & Mathews, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…), orchards several researchers have demonstrated the potential for companion plants to increase biological control (Bugg & Waddington, 1994;Jenser et al, 1997;Stephens et al, 1998;Brown & Glenn 1999;Bostanian et al, 2004). Enhancement of aphid biological control on apple has been accomplished with companion plants (Wyss, 1995;Brown et al, 1997) but other research has found no effect of companion plants on aphid populations (Gruys, 1982;Haley & Hogue, 1990;Brown & Glenn, 1999). Interplanting species of fruit trees bearing extrafloral nectaries into apple orchards has also been suggested (Brown & Mathews, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we test this hypothesis for the case of three phytoseiid species that are commonly found in Dutch apple orchards: Typhlodromuspyri (Scheuten ), A mblyseius finlandicus ( Oudemans ) and A. potentillae ( Garman ) (Overmeer, 1981;Gruys, 1982;McMurtry and van de Vrie, 1973). The major part of the diet of these predators consists of two phytophagous mite species that are considered to be pests (Easterbrook, 1979;Van de Vrie, 1973;Van Epenhuijsen, 1981;Gruys, 1982) and therefore far more abundant than any other potential prey species: the European red spider mite, Panonychus ulmi (Koch), and the apple rust mite, Aculus schlechtendali (Nalepa).…”
Section: Introductionmentioning
confidence: 99%
“…The major part of the diet of these predators consists of two phytophagous mite species that are considered to be pests (Easterbrook, 1979;Van de Vrie, 1973;Van Epenhuijsen, 1981;Gruys, 1982) and therefore far more abundant than any other potential prey species: the European red spider mite, Panonychus ulmi (Koch), and the apple rust mite, Aculus schlechtendali (Nalepa). Typhlodromus pyri and Am.…”
Section: Introductionmentioning
confidence: 99%
“…In such an approach, we are convinced that ABC can be applied much more than it is today, but we also know it will not solve all pest problems. A seriously neglected form of biological control, conservation biological control, should be the basis of most crop protection programs by providing sufficient invertebrate biological control agents and undisturbed buffering microbiomes in soils and plants when pests invade an agro-ecosystem (Gruys 1982;Blommers 1994;Berendsen et al 2012). Delaying or preventing sprays will result in the reduction of secondary pests that arise after killing natural enemies of pest organisms.…”
Section: And What Next?mentioning
confidence: 99%